VXLAN Analysis and Design for Interconnecting Different Locations at Khairun University - Abdullah, Saiful Do.; Lutfi, Salkin; Fuad, Achmad; Nur, Alan Wahyudin; Ibrahim, Adelina (Jambura Journal of Electrical and Electronics Engineering, 2024)
Khairun University is currently divided into 4 campuses with different geographical locations. The distance between these locations is very far, this results in each location having a network configuration that is not centralised. This research aims to connect networks in geographically different locations at Khairun University between Gambesi Campus and Jati Campus to be connected using one centralised IP segmentation. This research method consists of a literature study stage, a network topology design stage, a network simulation stage, a network simulation analysis stage, and a data analysis stage. Focusing on VXLAN to answer the challenge of how to connect two different locations between Gambesi campus and Jati campus to be connected in one location. By analyzing and designing through GNS3 with the help of VMWare virtualisation, VXLAN implementation can be done on proxy devices. This test uses ping, traceroute, packet capture, and throughput. The results of this study show that VXLAN itself implements several protocols that run at Layer 2 of the network, one of which is the Cisco Discovery Protocol (CDP). And throughput shows with a buffer size of 256 KB has a data transfer of 1.5 MB and a bandwidth of 1.26 Mbs, a buffer size of 512 KB has a data transfer of 2 MB and a bandwidth of 1.68 Mbs, and with a buffer size of 1024 KB has a data transfer of 2.5 MB and a bandwidth of 2.1 Mbps. In other words, VXLAN successfully connects computer networks in different locations with the same IP subnet. Although not directly connected to the internet, data transmission between clients in two geographically different locations was successful.